Review of Access Limits and Surcharge Policies. (Policy Papers; Policy Paper ;, 2016)
Scope and strategy: This paper reviews access limits and surcharge policies in the Fund's General Resources Account (GRA). It builds on the preliminary Executive Board discussion that took place in May 2014, against the backdrop of the 14th Review quotas expected to become effective early in 2016, which will on average double individual members' quotas. At the meeting in 2014, most Directors considered that a moderate increase in normal access limits in SDR terms would broadly restore the normal Fund access to levels considered acceptable in 2009, and saw merit in adjusting the surcharge threshold to allow for a moderate increase in the SDR value of credit not subject to the charge.